SY03-1-6NIDA-ISAM FELLOWSHIPA QUALITATIVE STUDY ON METHAMPHETAMINE RELATED SEXUAL HARM IN IRAN. (September 2014) - Farhoudian, A.; Dolatshahee, B.; Ahmadpour, N.; Sadeghi, M.; Tavackoli, M.; Farhadi, M. H.; Massah, O.; Dogahe, E. R.; Ardakani, M. R. K.; Shirinbayan, P.; Najafi, M. R.
Abstract : Aim. This study aimed to investigate the effects of methamphetamine use on male high risk sexual behaviors in public and private addiction treatment centers in Tehran. Methods. Using qualitative content analysis of their narrative responses, the statements of methamphetamine, users their spouses, psychiatrists or physicians who were acclaimed in addiction treatment and research were analysed. Results. Four main categories were determined in the responses of interviewees, each of which possesses a subclass. These classes included "different attitudes to sexual behavior", "different abilities and sexual risk behaviors", "the feeling to forced sex" and "difficulties in appropriate sexual behaviors". Considering these mechanisms, the methamphetamine use can predispose sexual risk behaviors in Iranian male addicts. Conclusion. Using metamphetamine seems to cause a sharp increase in sexual coercion, sexual risk behaviors and some deviations in one's sexual profile. The implications in preventing the prevalence of HIV infection, sexual education, and harm reduction were discussed.